Reliability and reproducibility of the Kinvent K-push dynamometer for assessing quadriceps strength and force development in athletes and untrained individuals - Trybulski, Robert; Więckowski, Jakub; Muracki, Jarosław; Matuszczyk, Filip; Gałęziok, Kamil; Wilk, Michał; Kużdżał, Adrian (Frontiers in Physiology, 2025)
ObjectivesThis study aimed to (1) analyze the reliability of the Kinvent K-push handheld dynamometer for assessing quadriceps maximum voluntary contraction (MVC) and rate of force development (RFD), and (2) evaluate inter-rater reliability by assessing the reproducibility of measurements between examiners.MethodsA blinded, randomized, comparative study evaluated the reliability of quadriceps femoris MVC and RFD measurements obtained by two independent researchers. Forty-four male volunteers participated, divided into three groups based on motor skill level: elite mixed martial arts (MMA) athletes (n = 15), amateur football players (n = 15), and untrained healthy volunteers (n = 14). Three measurements per leg were taken during the experimental session, with the Kinvent K-push handheld dynamometer automatically calculating the average MVC and RFD.ResultsPearson correlations revealed that MVC and RFD measurements were highly consistent, with the left quadriceps showing nearly perfect correlations (r = 0.96 for MVC, r = 0.97 for RFD), while the right quadriceps displayed more variability, particularly in MVC. Inter-examiner comparisons showed high reproducibility, with minimal differences between the two measurers (p > 0.05). The ICC further supported this, with very high intraclass correlation values, especially for RFD (ICC = 0.999), confirming almost perfect agreement between the measurers. Group comparisons revealed that athletes, particularly MMA fighters and footballers, had significantly higher muscle strength and RFD compared to the general non-training group (p < 0.05), with athletes showing similar values for both MVC and RFD, while the general non-training group exhibited greater variability in both parameters. Bland-Altman analysis revealed strong agreement between measurers across all quadriceps measurements, with minimal systematic bias and acceptable variability, particularly in MVC assessments.ConclusionMVC and RFD measurements in the quadriceps using the K-push handheld dynamometer are highly reliable and consistent, with minimal inter-examiner variability. These findings, in conjunction with high ICC and low MAE/MSE values, underscore the reliability of the measurement protocol used in this study. The tested instrument provides consistent and accurate results, ensuring reliable measurements across different examiners.